Restoration of intracellular drug accumulation in MDR cell line K562r does not mean reversal of its drug resistance - Hu Xun; Chen Wan-yuan (Acta Pharmacologica Sinica, 2016)
Our purpose was to test whether drug sensitivity and drug accumulation in MDR cell erythroleukemic K562r could be restored by incubating cells with 3 anthracycline antibiotics in combination. Drug sensitivities of cells were assessed with MTT assay, in which doxorubicin, epirubicin, daunorubicin, or the 3-drug mixture was applied with concentrations ranging from 1 to 3125 ng.ml-1. The IC50 of K562r cells were 1.0, 1.0, 0.1, and 0.2 microgram.ml-1, respectively, about 22, 16, 10, and 20 times higher than those of K562 cells. After cells were exposed to doxorubicin (2-32 micrograms.ml-1) for 1 h, the drug concentrations in K562r cells were all higher than those in K562 cells. Similar results were obtained for epirubicin or daunorubicin. After 1-h incubation of cells with the 3-drug mixture (3 to 192 micrograms.ml-1), there were no considerable differences of drug accumulation between K562r and K562 cells with only 3 exceptions in 21 groups. It is concluded that restoration of intracellular drug accumulation in MDR cell line K562r was not correlated with reversal of its drug resistances.